Effects of feeding frequency on growth in hatchery reared beluga sturgeon (Huso huso) - Mohseni, M.; Pourkazemi, M.; Bahmani, M.; Pour Ali, H.; Kazemi, R.; Salehpour, M. (2004)
The effects of feeding frequency on growth rate, food conversion ratio (FCR) and survival in juvenile beluga sturgeon were studied through two phases of rearing. 360 beluga fingerlings with an average weight of 20.51 ±0.33g were reared through a period of 60 days in the first phase and about 180 fingerlings with an average weight of 77.55±1.18g were reared through a period of 95 days in the second phase in fiberglass tanks (500 L) with a water flow rate of 0.2 L/sec under similar conditions of rearing (dissolved oxygen, light, water velocity, etc.). Three different feeding frequencies were used for each phase (3, 5 and 8 times feeding per day) with three replicates. It was evident from the results obtained from the first experimental phase that with an increase in feeding frequency there was an increase in growth rate, weight increase percentage and specific growth rate as well as a decrease in FCR value. However no significant differences were observed in the three group,) studied (P >0.05). Whereas in the second phase of study significant differences (P<0.05) were observed in the parameters studied (length, weight and FCR) in the third study group (with 8 times feeding per day) at the end of study period. We may therefore conclude that growth rate, nutritional uptake and social behavior of each fish species are dependent on its feeding frequency. Published